PENGARUH VOLUME BULI-BULI TERHADAP PANJANG PROSTAT PADA PEMERIKSAAN ULTRASONOGRAFI TRANSABDOMINAL - Ali, Zulfikar; Mochtar, Chaidir A (Indonesian Urological Association, 2009)
Objective: To study the effects of different bladder volumes on the length of prostatic protrusion as measured by transabdominal ultrasonography. Materials & Method: We did an observational study on 48 patients with BPH and urinary retention in Urology outpatient clinic of Cipto Mangunkusumo Hospital Jakarta from 1 March 2006 to 28 February 2007. The bladder of each patient was filled with 50 ml normal saline and increased stepwise by 50 ml each time until either an urge to void or a volume of 500 ml was reached. Length of prostatic protrusion was measured by transabdominal ultrasonography at each volume of bladder filling in every patient. Results: The average length of prostatic protrusion in 50, 100, 150, and 200 ml bladder filling was 11,14; 11,42; 11,88; 10,20 mm respectively. There is no statistically significant difference in the length of prostatic protrusion with transabdominal ultrasonography in each bladder volume. Conclusion: Prostatic protrusion length can be measured with bladder volumes between 50 ml to 200 ml and shows no significant difference.